Sustainable Agriculture on the Hillsides of Central America: Opportunities for Interinstitutional Collaboration: report on workshop - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The paper refers to experiments with green-manure crops that require little investment and are capable of growing in marginal soils under minimum tillage and it emphasizes since 1987, thousands of small-farm families in Honduras, Yucatan, and other countries adopted the system of intercrops, using Canavalia ensiformis and Stizolobium spp., and successfully introduced permanent crops in areas where slashing, clearing, and burning were practiced. The Program's goal was to triple production of basic traditional crops (such as maize) by using fertilizer obtained entirely on farms. The green-manure crops develop well in poor soils. (